Centro de atención integral de víctimas y población civil en el municipio de Algeciras - CAIVPC “Juntos” (2023)
The municipality of Algeciras, victims and the civilian population have been physically and psychologically affected by the armed conflict, due to these problems of violence, land grabbing, forced displacement, kidnapping, attacks, etc. They present psychosocial damage, a situation that directly impacts the mental and emotional health of the population, evidencing that the municipality presents a deficit of infrastructure and spaces for care, support, accompaniment, and rehabilitation.